STRATEGI PENGEMBANGAN WISATA PESISIR PANTAI: STUDI KASUS DESA BATU LIMA, KUALA TAMBANGAN KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Febrianty, Irma (Pusat Penelitian Sumberdaya Pesisir dan Laut, Universitas Maritim Raja Ali Haji, Indonesia, 2017)
Pantai Batu Lima is located in the village of Tanah Laut Kuala Tambangan. This beach has natural beauty in addition there is also a cultural element to be preserved, but the public interest is still low for a visit to Batu Lima, to further develop the need for management strategies Pantai Batu Lima. The purpose of this study to identify the potential for coastal tourism Pantai Batu Lima and its development strategy. The analysis used in this research is SWOT analysis. Results of this study showed potential of the coastal resources i.e. sloping beach, culture badudus bathing on the beach, lodging facilities, playground and seating on the beach.